"How Would We Deserve Better?" Rural–Urban Dichotomy in Health Seeking for the Chronically Ill Elderly in China. (October 2016) - Long, Yan; Li, Lydia W.
As China's older adult population has rapidly increased, the attending increase in chronic disease poses serious concerns regarding disparities in medical care utilization for elders. Drawing on 48 semistructured interviews with elders with chronic conditions and their caregivers in China, this article analyzes two opposite patterns of health-seeking behavior in urban and rural areas. Presenting the findings as a relational model, we argue that the interplay between structures of medical care and cultural discourses about health and (un)worthiness generates different habitus as sets of practices and beliefs that facilitate or hinder elders' and their caregivers' decisions to engage with medical care. By demonstrating the Chinese state's social health insurance reform's failure to improve health-seeking behavior on the ground, our findings suggest that efforts to understand and promote health-seeking behavior need to address the intersections of structural and cultural factors.